Meta-analysis of perioperative antibiotics in patients undergoing laparoscopic cholecystectomy. Issue 1 (2nd September 2015) - Pasquali, S; Boal, M; Griffiths, E A; Alderson, D; Vohra, R S
Abstract: Background: The effectiveness of perioperative antibiotics in reducing surgical-site infection (SSI) and overall nosocomial infections in patients undergoing laparoscopic cholecystectomy for biliary colic and low- and moderate-risk cholecystitis (Tokyo classification) is unclear. A systematic review and meta-analysis was performed to assess this. Methods: Searches were conducted of the MEDLINE, Embase and Cochrane databases. Only randomized clinical trials (RCTs) were included. The analysis was performed using the random-effects method, and the risk ratio (RR) with 95 per cent c.i. was employed. Results: Nineteen RCTs, published between 1997 and 2015, with a total of 5259 participants, of whom 2709 (51·5 per cent) were treated with antibiotics, were included. SSI and overall nosocomial infections were detected in 2·4 and 4·2 per cent respectively of patients given perioperative antibiotics, and in 3·2 and 7·2 per cent of those who received no antibiotics. Antibiotics did not significantly reduce the risk of SSI (RR 0·81, 95 per cent c.i. 0·58 to 1·13; P = 0·21) or overall nosocomial infections (RR 0·64, 0·36 to 1·14; P = 0·13). There was no significant between-study heterogeneity for SSI, but significant between-study heterogeneity in the eight studies that reported nosocomial infections. Analysis of studies considered to be high quality, grouped according to the timing of antibiotics (preoperative only or perioperative) and reporting intention-to-treat analyses, again failed to show a significant reduction in SSI. Conclusion: Antibiotics should not be administered before laparoscopic cholecystectomy in patients with biliary colic and/or low- and moderate-risk cholecystitis. Abstract : Unnecessary for many patients